The academic achievement of Southeast Asian foreign students enrolled for the academic years 1960-1961 through 1964-1965 in the University of the Philippines - Lee, Byong-Hee 1940- (s.n.], 1965)
This study looked on the academic achievements of Southeast Asian foreign students enrolled for the academic years 1960-1961 through 1964-1965, at the University of the Philippines. Results show that the chances of these students dropping out from UP are greater after their first two semesters than at any other time during their stay in the institution. These and some other findings with regards to academic achievement are presented in this study.